Management of Parenting Activities as an Effort To Improve Early Children's Development - Wahidah, Finadatul; Fitriya, Anita; Soleha, Wardatus (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
This research describes program management parenting to improve children's development in Early Childhood Education (PAUD), with focus on how to plan, implement, and evaluation of parenting programs. Through approach qualitative, this research involves participant observation, in-depth interviews and document analysis for dig up data from the object institution study. The research results show that the process. Parenting activities at TK Dharma Wanita 03 positively impact increasing parental participation and understanding of effective parenting patterns. Through a series of activities involving parents, such as seminars and recreation. The evaluation of parenting programs is also a focus of this research. By collecting data through surveys and interviews, evaluations are carried out to assess the extent to which the program has achieved its objectives. The evaluation results show a significant increase in participation and understanding of parents. The parenting activity program implemented at TK Dharma Wanita 03 Sukorambi Jember impacts children's development, including a. Children's social-emotional development; b. Moral and Religious Development.